THE EFFECT OF SERVICE, PRICE, DELIVERY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT PT. DISTRINDO JEMBER - Ridhotama, Firli Adri; Widnyani, Ni Made (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to analyze the influence of service quality, price, on-time delivery, and product quality on customer satisfaction at PT. Panahmas Dwitama Distrindo in Jember. This research is quantitative with a causal approach. The study population was all customers of PT. Panahmas Dwitama Distrindo, with a sample size of 100 respondents determined using accidental sampling. Data analysis techniques used were multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that partially, service quality, price, on-time delivery, and product quality have a positive and significant effect on customer satisfaction. Simultaneously, these four variables also significantly influence customer satisfaction with an R² value of 0.813, meaning that 81.3% of the variation in customer satisfaction can be explained by the independent variables, while the remaining 18.7% is influenced by other factors outside the study. These findings emphasize the need for companies to improve service quality, competitive pricing, maintain on-time delivery, and consistent product quality to maintain and enhance customer satisfaction.